2014
DOI: 10.1111/cen.12384
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of thyroid hormones between impaired fasting glucose and impaired glucose tolerance: free T3 affects the prevalence of impaired fasting glucose and impaired glucose tolerance in opposite ways

Abstract: Free thyroid hormone levels were different between subjects with IFG and IGT. FT3 affects the prevalence of IFG and IGT in opposite ways. The difference in thyroid hormone levels may play an important role in the different pathological mechanisms of IFG and IGT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…Previous studies have noted a correlation between TH levels and insulin signaling. For example, in humans the prevalence of impaired fasting glucose increases linearly with levels of fT 3 , and impaired glucose tolerance decreases with levels of fT 3 (22). The present study demonstrated that neither insulin nor glucose infusions remarkably altered any of the plasma thyroid hormones over the course of the measurement period.…”
Section: Discussioncontrasting
confidence: 38%
“…Previous studies have noted a correlation between TH levels and insulin signaling. For example, in humans the prevalence of impaired fasting glucose increases linearly with levels of fT 3 , and impaired glucose tolerance decreases with levels of fT 3 (22). The present study demonstrated that neither insulin nor glucose infusions remarkably altered any of the plasma thyroid hormones over the course of the measurement period.…”
Section: Discussioncontrasting
confidence: 38%
“…In adipose tissue of obese subjects, the expression of DIO1 was upregulated through the stimulation of leptin ( 37 ). Several previous studies reported that increased FT3 and FT3/FT4 ratio were associated with unfavorable metabolic phenotypes, including higher BMI, TC, BP, and FPG ( 38 40 ). Our study found a higher conversion of FT4 to FT3 in patients with prediabetes, though it did not reach significance after adjusting for BMI, WC, dyslipidemia, and hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Higher FT3 and serum thyroid-stimulating hormone levels were related to a decreased risk of TN in female subjects, while higher FT4 level was related to an increased risk of TN in male subjects. A recent study reported that FT3 and FT3/FT4 were positively related to BMI, waist, TG, and FPG, while FT4 was negatively related to the above metabolic parameters [ 45 ]. Few studies have explored this apparent paradox between the free THs (thyroid hormones) and TN.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, although the difference of the study populations might be responsible for the above inconsistency, it was still difficult to explain the independent association between TN formation and the free THs levels. A possible explanation could be that free T3 and free T4 might be affecting the prevalence of MetS in opposite ways [ 45 47 ]. In addition, our study should be acknowledged with several potential limitations.…”
Section: Discussionmentioning
confidence: 99%